1972
DOI: 10.1111/j.1432-1033.1972.tb01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification and Kinetic Studies on Glucarate Hydro‐Lyase from a Species of Pseudomonas A

Abstract: Glucarate hydro‐lyase, obtained from cells of Pseudomonas A grown on glucarate as the sole source of carbon, was purified 40‐fold in 70% yield. The effects of a variety of chemical modifiers and competitive inhibitors on the enzyme activity were studied. Enzyme activity was irreversibly lost by incubating the enzyme with p‐chloromercuribenzene sulphonate. (+)‐Tartrate, a competitive inhibitor of the enzyme, protected the enzyme from inhibition by this reagent but was not effective when the enzyme was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…10013 was obtained from the National Collection of Industrial Bacteria, Torry Research Station, Aberdeen, U.K. The organism was maintained and grown under conditions identical with those described by Jeffcoat (1972). Protein was determined with reference to bovine serum albumin (BDH Biochemicals, Poole, Dorset, U.K.) from a calibration curve prepared by the method of Lowry et al (1951).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…10013 was obtained from the National Collection of Industrial Bacteria, Torry Research Station, Aberdeen, U.K. The organism was maintained and grown under conditions identical with those described by Jeffcoat (1972). Protein was determined with reference to bovine serum albumin (BDH Biochemicals, Poole, Dorset, U.K.) from a calibration curve prepared by the method of Lowry et al (1951).…”
Section: Methodsmentioning
confidence: 99%
“…Glucarate hydrolyase from Ps. acidovorans was assayed as described by Jeffcoat (1972). 4-Deoxy-5-oxoglucarate aldolase activity was measured by a coupled assay with 10 units of pig heart lactate dehydrogenase [Boehringer Corp. (London) Ltd., London W.5, U.K.], 0.5,umol of NADH, 1,umol of oxodeoxyglucarate, 501umol…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently little evidence was available to suggest that any other enzyme could be classified in this way, but there is now increasing support that such similarities also exist between hydro-lyases isolated from different sources. This stems from the isolation of Mg2+dependent hydro-lyases (Blumenthal & Fish, 1963;Jeffcoat, 1972) and Schiff-base-forming hydro-lyases (Portsmouth et al, 1967;Jeffcoat et al, 1969). Closer links between aldolases and hydro-lyases are now emerging, since preliminary observations have suggested that metal-ion-dependent aldolases (Morse & Horecker, 1968) and Mg2+-dependent hydrolyases (Jeffcoat, 1972) utilize the formation of a metal-containing ring structure in the enzymesubstrate complex, and Jeffcoat (1974) has demonstrated the Mg2+-dependent aldol cleavage of 4deoxy-5-oxoglucarate by glucarate hydro-lyase.…”
mentioning
confidence: 99%